The Switched Reluctance Electric Machine with Constructive Asymetry - Alexander Petrushin; Maxim Tchavychalov; Ekaterina Miroshnichenko (Institute of Advanced Engineering and Science, 2015)
Results of researches of forces of a unilateral attraction of a rotor to a stator of switched reluctance electric machines taking into account unevenness of an air gap are given. It is offered for configurations of magnetic systems with weak magnetic communication between the coils making a phase to carry out a supply of coils in parallel or independently from each other for reduction of not compensated forces of a unilateral attraction of a rotor to a stator.